Omalus Panzeri 1801 - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
2. Genus Omalus Panzer, 1801 Omalus Panzer 1801: 13. Type species: Chrysis aenea Fabricius, 1787 [= Omalus aeneus (Fabricius, 1787)], by monotypy. : Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on page 9, DOI: 10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433 : {"references": ["Fabricius, J. C. (1787) Mantissa Insectorum sistens eorum species nuper detectas adiectis characteribus genericis, differentiis, specificis, emendationibus, observationibus. Tom. I. Impensis Christ. Gottl. Froft., Hafniae, xx + 348 pp. http: // dx. doi. org / 10.5962 / bhl. title. 11657"]}